Concentration and Size Distribution of Fungi Aerosol over Oceans along a Cruise Path during the Fourth Chinese Arctic Research Expedition - Juan Yu; Qihou Hu; Zhouqing Xie; Hui Kang; Ming Li; Zheng Li; Peipei Ye (Atmosphere, 2013)
Bioaerosol can act as nuclei and thus may play an important role in climate change. During the Fourth Chinese National Arctic Research Expedition (CHINARE 2010) from July to September 2010, the concentrations and size distributions of airborne fungi, which are thought to be one of important bioaerosols, in the marine boundary layer were investigated. The concentrations of airborne fungi varied considerably with a range of 0 to 320.4 CFU/m3. The fungal concentrations in the marine boundary layer were significantly lower than those in most continental ecosystems. Airborne fungi over oceans roughly displayed a decreasing trend with increasing latitudes. The mean concentrations of airborne fungi in the region of offshore China, the western North Pacific Ocean, the Chukchi Sea, the Canada Basin, and the central Arctic Ocean were 172.2 ± 158.4, 73.8 ± 104.4, 13.3 ± 16.2, 16.5 ± 8.0, and 1.2 ± 1.0 CFU/m3, respectively. In most areas airborne fungi showed a unimodal size distribution pattern, with the maximum proportion (about 36.2%) in the range of 2.1~3.3 µm and the minimum proportion (about 3.5%) in the range of 0.65~1.1 µm, and over 50% occurred on the fine size (<3.3 µm). Potential factors influencing airborne fungal concentrations, including the origin of air mass, meteorological conditions, and sea ice conditions, were discussed.